2019
DOI: 10.1016/j.jjcc.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of warfarin and dabigatran in patients with non-valvular atrial fibrillation in Japan: A claims database analysis

Abstract: Background: Antithrombotic therapy, including direct oral anticoagulants, is recommended in patients with non-valvular atrial fibrillation (NVAF) who are at intermediate-to-high risk of stroke. The aims of this study were to assess the patterns of oral anticoagulant (OAC) prescription in Japanese patients with NVAF and compare the effectiveness and safety of dabigatran and warfarin. Methods: This was a retrospective observational study of adults with NVAF who initiated dabigatran or warfarin between March 14, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…The ORBIT and ATRIA scores both consist of five factors, including a history of anemia/bleeding (in both scores) and antiplatelet use (in the ORBIT score). However, the prevalence of these factors was relatively low (2.1% and 5.8%, respectively) [10] and the impact of these factors would be relatively small. On the other hand, neither the ORBIT nor ATRIA scores included hypertension (which had a high prevalence rate and a relatively high hazard ratio) as a factor for the risk assessment.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The ORBIT and ATRIA scores both consist of five factors, including a history of anemia/bleeding (in both scores) and antiplatelet use (in the ORBIT score). However, the prevalence of these factors was relatively low (2.1% and 5.8%, respectively) [10] and the impact of these factors would be relatively small. On the other hand, neither the ORBIT nor ATRIA scores included hypertension (which had a high prevalence rate and a relatively high hazard ratio) as a factor for the risk assessment.…”
Section: Discussionmentioning
confidence: 94%
“…The bleeding risk in AF patients who undergo anticoagulant therapy has been evaluated using various scoring systems, including the HAS-BLED [Hypertension, Abnormal renal/liver function, Stroke, Bleeding history or predisposition, Labile international normalized ratio (INR), Elderly, Drugs/alcohol] [5], HEMORR 2 HAGES [6], ATRIA (AnTicoagulation and Risk Factors In Atrial Fibrillation) [7], and ORBIT (Outcomes Registry for Better Informed Treatment) [8] scores. Warfarin was once the predominant anticoagulant used for AF but has been largely supplanted by direct oral anticoagulants, and the bleeding risks associated with both types of anticoagulants have been investigated in AF patients [9,10]. The usefulness of the risk stratification according to the modified (m)HAS-BLED score, which is the HAS-BLED score without the INR, in patients taking direct oral anticoagulants, has been reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…Administrative healthcare databases have been increasingly used for studies to investigate treatment patterns, patient demographics, healthcare resource use, and treatment cost, as well as to estimate the effectiveness and safety of medicinal products in the real world clinical setting. [1][2][3][4][5][6] In Japan, claims databases became available for commercial use in the early 2000s, 7 and the government has constructed a database containing administrative claims from the entire Japanese population, and these data are currently provided to academia on request. 4,5 Hospitals are adopting the diagnostic procedure combination/per-diem payment system (DPC/PDPS) in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Databases consisting of claims data from these DPC hospitals are commercially available, and have been used for various clinical studies. [1][2][3]6 In the field of diabetes treatment, several real-world evidence studies have been published using these large claims databases, including Japanese data from DPC hospitals. These studies typically evaluate the effectiveness of diabetes drugs in reducing the occurrence of cardiovascular outcomes such as hospitalized heart failure, stroke, myocardial infarction and cardiovascular and all cause death.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of demographic characteristics in this database is similar to the general Japanese population. The validity of this database for epidemiological research in NVAF has been demonstrated 19 , and it was used in recent studies 17,20 .…”
Section: Data Source and The Japanese Health-care Systemmentioning
confidence: 99%